PENGARUH SELEKSI REKRUTMEN DAN PENEMPATAN KERJA TERHADAP PRESTASI KERJA KARYAWAN BAGIAN PEMASARAN PT ASURANSI JIWASRAYA (PERSERO) CABANG BANJARMASIN - Faridawati Erlina (Administraus, 2018)
This research aims: 1) To determine the effect of selection partially on Employee Job Performance of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin. 2) To determine the effect of recruitment partially on Employee Job Performance of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin. 3) To determine the effect of job placement partially on Job Performance Employees of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin, and 4) To determine the effect of selection, recruitment and job placement simultaneously towards Job Performance Employees of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin. The method used in this research is descriptive quantitative. The population in this study were all employees of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin is 75 people. Sampling in this research was done by using random sampling withdrawal. Data were collected through questionnaires, observation and documentation. Results showed that: (1) Selection of a positive influence and significant impact on Employee Job Performance of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin, namely 49.5%. (2) Recruitment provides a positive and significant effect on Employee Job Performance of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin, namely 38.1%. (3) Employment provide a positive and significant effect on Employee Job Performance of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin, namely 79.9%. (4) The selection, recruitment and job placement simultaneously have a positive influence and significant impact on Employee Job Performance of Marketing Departement Asuransi Jiwasraya Inc Branch Banjarmasin which amounted to 57.8%